PENGARUH MODEL TEAM GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN KOLABORASI PESERTA DIDIK KELAS XII-C2 DI SMA NEGERI 11 SEMARANG PADA MATERI REAKSI REDUKSI DAN OKSIDASI - Nur Fauziah; Endang Triwahyuni Maharani; Tuti Hendrawati (LitbangMu Jawa Tengah and Teacher Professional Education UNIMUS, 2024)
This study aims to determine the effect of the Team Games Tournament (TGT) model on the collaboration skills of the XII-C2 grade students at SMA Negeri 11 Semarang on the topic of reduction and oxidation reactions. The research method used is a mixed method with a Classroom Action Research (CAR) design. The steps of this Classroom Action Research include plan, act, observe, and reflect. The implementation period of the Classroom Action Research is from October 18, 2024, to November 19, 2024. The subjects of this research are 36 students from class XII-C2 at SMA Negeri 11 Semarang. The technique for collecting data is the observation technique. The quantitative data analysis techniques used are descriptive statistics and the Paired T-Test. This data analysis is conducted to test the effect of the TGT model on students' collaboration skills. The research indicating a significant improvement in the collaboration skills of class XII-C2 students using the TGT learning model implemented in cycle 2. Based on anecdotal records, students with high collaboration skills tended to be active in participating in learning during cycles 1 and 2. On the other hand, students with low collaboration skills need more support and guidance from the teacher.